1999
DOI: 10.1097/00000372-199906000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Fibroblastoma (Collagenous Fibroma)

Abstract: Desmoplastic fibroblastoma is a vary rare subcutaneous proliferation. We describe a case of desmoplastic fibroblastoma in a 24-year-old Korean woman who presented with a 2.5 cm solitary and firm nodule on her back which had been present for 3 months. Histologic studies showed a well demarcated subcutaneous tumor composed of stellate or spindle shaped cells embedded in hypovascular fibrous or fibromyxoid stroma. No mitotic figures, calcification, or necrosis were observed. The stellate or spindle shaped cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…Microscopically, DF is characterized by a paucicellular proliferation of spindle to stellate-shaped cells, embedded in a highly hyalinized collagenous stroma with or without focal fibromyxoid degeneration [4]. Binucleation [3,6] and a few multinucleated giant cells can be observed in some reports [1,3,[20][21][22], as was the case in the present study. However, future research concerning the exact origin of multinucleated giant cells is warranted.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Microscopically, DF is characterized by a paucicellular proliferation of spindle to stellate-shaped cells, embedded in a highly hyalinized collagenous stroma with or without focal fibromyxoid degeneration [4]. Binucleation [3,6] and a few multinucleated giant cells can be observed in some reports [1,3,[20][21][22], as was the case in the present study. However, future research concerning the exact origin of multinucleated giant cells is warranted.…”
Section: Discussionsupporting
confidence: 77%
“…The majority of studies containing a-smooth muscle actin have shown that lesional cells are focally positive [3, 5, 6, 19-21, 23, 24]. However, as occurred in the present research, other studies have also reported negative a-smooth muscle actin [1,22,25,26]. Factor XIIIa proved to be positive in only a few selected cells [3,6,26], while negative staining could be observed in one study [1].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…It usually appears in various locations, including the upper extremities, posterior neck, upper back, lower extremities, abdominal wall and hip. The tumor ranges in size from 1 to 20 cm in maximum dimension [3,4]. Entrapment of the adjacent muscle and fat is common, but aggressive growth is not a feature of desmoplastic fibroblastoma [1,3,5].…”
Section: Discussionmentioning
confidence: 99%